O agostinismo político: contribuições e limites para as discussões políticas medievais - Souza, Luciano Daniel de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This study was carried out to analyze Henri-Xavier Arquillière's political Augustinism (1883-1956), in order to understand the historical moment in which he formulated that historical category for the medieval politics. For Arquillière, Saint Augustin's political thought was inverted in its fundamental aspects propitiating interpretive versions. Aquillière, French historian, argued in 1934 that the political thought followed by Gregorius VII and other Popes was based on the political Augustinism. According to Aquillière, the political Augustinism was contested on the basis that it was a neoThomist and apologetical version of the papacy 's actions. Within that context, one tried to understand whether the assertions on Saint Augustin's importance might be relegated due to its institutional connection with the author. Certeau, in his conception about the social role played by the historian, contributes to such a thesis pointing out that every historian starts from an institution which assigns legitimacy and authenticity to his/her historiography. Such a thesis is unfolded, at first, in order to know Aquillière's academic background, historiography, and textbooks. The French historian, by disclosing features of the methodical school, expanded the political Augustinism as an explanatory reading of medieval politics thus exposing himself to generalization problems. Aquillière wrote textbooks in which he introduced political Augustinism to young people aiming at explaining his teachings on the Catholic Church, redeeming its importance in the political and religious background of his time. By analyzing A Cidade de Deus, one notices in Saint Augustin's writings benevolent attitudes toward the Roman Empire and the lack of assertions which gave support to a papal monarchy. NeoThomism at the time Aquillière formulated the political Augustinism was an active movement within the Catholic Church, it allowed a careful examination of Augustinian ...

O presente estudo analisa o agostinismo político de Henri-Xavier Arquillière (1883-1956), a fim de compreender o momento histórico em que ele formulou essa categoria histórica para a política medieval. Para Arquillière, o pensamento político de Santo Agostinho foi invertido em aspectos fundamentais criando versões interpretativas. Arquillière, historiador francês, defendeu em 1934 que o pensamento político de Gregório VII e de outros papas guiava-se pelo agostinismo político. O agostinismo político como exposto por Arquillière foi contestado como sendo uma versão neotomista e apologética das ações do papado. Neste contexto, buscou-se compreender se as afirmações sobre a importância de Santo Agostinho podiam ser desprezadas pelo motivo da vinculação institucional do autor. Certeau, em sua concepção de lugar social do historiador, contribui nesta tese para apontar que todo historiador parte de uma instituição que o legitima e confere autenticidade à sua historiografia. Esta tese desdobra-se, num primeiro momento, para conhecer a formação acadêmica, a historiografia e os livros didáticos de Arquillière. O historiador francês, possuindo traços da escola metódica, expandiu o agostinismo político como uma chave de leitura da política medieval expondo-se, assim, aos problemas de uma generalização. Arquillière escreveu manuais didáticos nos quais expôs o agostinismo político para os jovens com a intenção de ensinar sobre a Igreja Católica, resgatando a importância dela no cenário político e religioso de seu tempo. Por meio da análise da obra A Cidade de Deus, percebe-se em Santo Agostinho posições benévolas ao Império Romano e à ausência de afirmações que sustentassem uma monarquia papal. O neotomismo na época em que Arquillière formulava o agostinismo político foi um movimento ativo na Igreja Católica, possibilitou o aprofundamento dos estudos agostinianos e contribuiu para resgatar o ...
Keywords: Igreja Catolica - Historia; Idade Media - Historia; Papado - Historia; Cristianismo e politica; Religião e politica; History